Students’ perception of community as classroom for learning Geography in middle secondary school - Karma Sonam Rigdel; Mani Raj Thapa (International Research Journal of Science, Technology, Education, and Management)
It is crucial to collaborate with the local community for learning to assist students in understanding reality given the changing needs of the world. By considering this perspective, a community-centred approach is embedded within local to global contexts to enhance students’ learning and civic development. However, the Department of Curriculum and Professional Development (2019) revealed that Community-Based Learning is rarely integrated into Geography lessons. Given these contexts, the present study seeks to explore the use of Community as Classroom (CAC) as a teaching strategy in learning Geography in middle secondary schools. As guided by pragmatism, a mixed-method design is applied to assess the students’ perceptions of the use of CAC as a learning strategy. The study also explored the relationship between the use of CAC strategy and students’ learning outcomes, opportunities, challenges and relevancy of CAC in the Bhutanese Geography curriculum. The survey questionnaires were administered to 264 students and four focus group interviews consisting of 6 members in a group were conducted and employed a purposive sampling strategy. Responses were analyzed using statistical and thematic analysis followed by triangulation of the quantitative and qualitative findings. The study revealed that the CAC strategy was relevant in enhancing social and academic standards. The findings indicated that the communities have abundant resources and the use of CAC strategy has imperative opportunities. However, this potential is hindered by several challenges. Moreover, the findings are consistent with the Bhutan Baccalaureate which considered community inclusion towards the creation of a knowledgeable and sustainable society.